Genetic reprogramming of cord blood derived endothelial colony forming cells towards human induced pluripotent stem cells using episomal plasmids - Osama Shahid; Sumbul Shamim; Jahan ara Ainuddin; Mohsin Wahid (Journal of the Pakistan Medical Association, 2021)
Objective: This study aimed to isolate human umbilical cord blood derived endothelial colony forming cells (ECFCs) followed by their integration free reprogramming towards induced pluripotent stem cells (iPSCs) and molecular characterization of both cell types using multicolor flowcytometery and immunofluorescence respectively. Methods: The cord blood was collected from 37-39 weeks of gestational ages after C-section ex-utero from Dow University Hospital. The ECFCs isolated after ficoll based separation of cord blood mononuclear cells (CBMNCs) which on emergence characterized through flow cytometry and reprogrammed towards induced pluripotent stem cells (iPSCs) using episomal vectors, the iPSCs were characterized using immunofluorescence. The study was conducted at Stem Cells and Regenerative lab, Dow Research Institute of Biotechnology and Biomedical Sciences, Dow University of health sciences OJHA campus. The study time duration was about one year (October 2017-October 2018), study design was in vitro experimental. The sample size of the study was n=3. Results: The isolated ECFCs were evaluated using Flowcytometery which showed positive expression for CD31, CD34, CD146 cell surface markers and negative for CD90. The successful reprogramming of ECFCs towards iPSCs was confirmed by immunofluorescence using OCT-4 which is considered to be a master regulator of pluripotency. Conclusion: To the best of our knowledge this study was the first attempt to integration free reprogramming of cord blood derived endothelial colony forming cells towards induced pluripotent stem using Episomal plasmids. Cells that have been isolated from cord blood and those that have been reprogrammed both have potential therapeutic applications in regenerative medicine. Continuous...